Swedish and American studies show that initiatives to decrease maternal obesity could play a key role in reducing preterm birth1. (25th March 2014) - Gould, Jeffrey B.; Mayo, Jonathan; Shaw, Gary M.; Stevenson, David K.; ,
Abstract Maternal obesity is a major source of preventable perinatal morbidity, but studies of the relationship between obesity and preterm birth have been inconsistent. This review looks at two major studies covering just under 3.5 million births, from California, USA, and Sweden. Conclusion Inconsistent findings in previous studies appear to stem from the complex relationship between obesity and preterm birth. Initiatives to decrease maternal obesity represent an important strategy in reducing preterm birth.